Profile of Students’ Problem-Solving Skills on Redox Reactions Using PBL-Based E-Worksheet - Himmah, Rifdah Fa’iqotul; Hidayah, Rusly (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to determine the profile of students’ problem-solving skills in redox reaction material assisted by E-Worksheet based on problem-based learning. This study is descriptive in nature, using a preliminary research method with data collection techniques carried out using student interview questionnaires, teacher interviews, and preliminary problem-solving skill tests given to students. The data obtained were analyzed descriptively, both qualitatively and quantitatively. This study was conducted on 26 students majoring in mathematics and natural sciences at Semen Gresik High School in Gresik City. The results based on the initial problem-solving skills test showed that the problem-solving skills of the 26 students were still lacking, with a percentage of 74.35% for understanding problems, 51.23% for planning, 51.23% for implementing plans, and 34.61% for evaluation. Based on a questionnaire related to learning media needs filled out by students, it was found that the majority of students (88.5%) still relied on textbooks as their main source of learning. Meanwhile, the use of Student Worksheet was recorded at 46.2%, and only 23.1% had ever used E-Worksheet. This shows that the use of E-Worksheet is still relatively low in the learning process. Chemistry teachers at the school also stated that the problem-based learning model had been implemented, but there were still obstacles, one of which was the difficulty in finding real-life problems that were relevant to chemistry material. Therefore, E-Worksheet is needed as a more accessible learning medium to improve students’ problem-solving skills in redox reaction material.